Chromosomal regions controlling resistance to gastro-intestinal nematode infections in mice - Iraqi, F.A.; Behnke, J.M.; Menge, D.M.; Lowe, A.M.; Teale, A.J.; Gibson, John P.; Baker, L.R.; Wakelin, D.R. (Springer, 2003)
Quantitative trait loci (QTL) associated with resistance to an intestinal worm in a well-defined murine model are described. These have been identified in an F(2) population derived from resistant (SWR) and susceptible (CBA) parental mouse strains infected with the gastro-intestinal nematode parasite Heligmosomoides polygyrus. Seven QTL located on six chromosomes are described, associated with components of the complex host response and the differential regulation of parasite survival and reproduction. The combined additive effects of the five significant QTL associated with worm survival (total worm count at necropsy) account for about 60% of the difference in worm count between the parental lines. The dominance effect for these five QTL are all in the direction of resistance, supporting the heterosis for resistance established from the mean worm count for the F(2) line relative to the parental lines. It is now possible to identify the comparative chromosomal regions of these QTL in livestock and humans and to consider the possibility of future improved control strategies. These may include breeding of resistant or tolerant livestock, development of vaccines, or identification of new anthelmintic drugs. [Journal Article; In English; United States]